Evaluation of Free Cooling Technique at the Telecom Cell Site in Ghana - Boakye, Kojo; Ohene Adu, Shiphrah; Nunoo, Solomon; Boakye, Kwaku (European Scientific Journal, ESJ, 2024)
Air Conditioning (AC) is the primary source of cooling in a typical Cell Site (CS) although it consumes a large quantity of electricity. Excessive energy consumption due to air conditioning increases the operational expenses of telecommunication companies. Therefore, network operators have attempted various techniques to reduce the exorbitant cost of a cell site’s high-power consumption. A Free Cooling (FC) System is one such approach. This paper uses computer modeling to investigate how the FC System will function at a CS in Ghana for 12 hours (from 6 pm to 6 am). A shelter with dimensions of 3 m × 2.47 m × 2.45 m (L × B × H) is used in the study, with three window positioning scenarios (different window heights), namely: (a) an inlet window 0.5 m high, and the outlet window 1.5 m high, (b) an inlet window and outlet window both 1.0 m high and (c) an inlet window 1.5 m high, and the outlet window 0.5 m high. The analysis revealed that the shelter with inlet and outlet windows at the same height has the most efficient heat dissipation potential. Furthermore, at a set temperature threshold of 25 °C, the annual percentage share for the two operating modes is approximately 67% for AC and 33% for FC in 2020, 76% for AC and 24% for FC in 2021, and 61% for AC and 39% for FC in 2022. However, when the set temperature threshold is increased from 25 °C to 30 °C, the annual percentage share is approximately 0.01% for AC and 99.9% for FC in 2020, 0% for AC and 100% for FC in 2021, and 1% for AC and 99% for FC in 2022. Thus, the proportion of free cooling increases as the set temperature threshold is raised, indicating potential energy savings. It could be concluded that in Ghana, installing a cell site with an FC system and setting the temperature of its control system to 30 °C or higher will result in significant energy savings.